Gout in the Chest Misdiagnosed as Ankylosing Spondylitis - Xue, Wenjing; Zhang, Shengkai; Wang, Qinqin; Que, Wenzhong; Xu, Shanghua (Frontiers in Medicine, 2020)
Gout is a crystal related joint disease caused by single sodium urate deposition in the joints or in soft tissues. In recent years, the incidence of gout has increased, but cases of urate crystals deposited in the chest-ribs are rare. Here we describe a 39-year-old man who complained of frequent pain and a feeling of tightness in chest-rips, and was misdiagnosed as ankylosing spondylitis. In addition, treatment with NSAID and Etanercept for six months showed no improvement, which confirmed the misdiagnosis. After physical examination, blood examination and double energy CT examination, the patient was diagnosed with gout and received correct treatment. In conclusion, gout in the chest and ribs is an unusual manifestation and has rarely been reported in the literature. This case highlights an important but overlooked history of hyperuricemia in the diagnosis, and dual energy CT is the preferred method for differential diagnosis of chest-ribs gout.